Endothelial progenitor cells and vascular endothelial growth factor after endovascular interventions in patients with type 2 diabetes - Marina Sergeevna Michurova (Endocrinology Research Centre, 2017)
Aim. To study the quantity of endothelial progenitor cells (EPCs) and levels of vascular endothelial growth factor A (VEGF-A) in patients with type 2 diabetes mellitus (T2DM) after endovascular interventions on coronary and peripheral arteries. Materials and methods. We observed 68 patients with stable angina pectoris and critical limb ischaemia, admitted for elective percutaneous coronary intervention and endovascular revascularisation of the lower extremity. The number of CD34+VEGFR2+CD45- and CD34+CD133+CD45- cells and levels of VEGF-A were determined before endovascular intervention and 2–4 days after the surgery. Results. We found that in patients without diabetes, the levels of EPCs increased significantly after endovascular interventions (CD34+VEGFR2+CD45-cells, p < 0.0001; CD34+ CD133+CD45-cells p = 0.041). The levels of EPCs in the peripheral blood of patients with T2DM before and after endovascular interventions did not significantly differ. The analysis of VEGF-A showed a statistically significant increase after intervention in both groups. In addition, in patients with an HbA1c level of <8% and duration of diabetes of <10 years, the levels of EPCs significantly increased (p = 0.001 and 0.005, respectively). In patients with an HbA1c level of ≥8% and duration of diabetes of >10 years, the levels of EPCs before and after endovascular interventions did not significantly differ. Conclusions. Patients with diabetes exhibited impaired EPC mobilisation after endovascular interventions. Poor glycaemic control and a long duration of diabetes are among the risk factors of EPC mobilisation.